18F‐AV‐1451 and CSF T‐tau and P‐tau as biomarkers in Alzheimer's disease. Issue 9 (25th July 2017) - Mattsson, Niklas; Schöll, Michael; Strandberg, Olof; Smith, Ruben; Palmqvist, Sebastian; Insel, Philip S; Hägerström, Douglas; Ohlsson, Tomas; Zetterberg, Henrik; Jögi, Jonas; Blennow, Kaj; Hansson, Oskar
Abstract: To elucidate the relationship between cerebrospinal fluid (CSF) total‐tau (T‐tau) and phosphorylated tau (P‐tau) with the tau PET ligand 18 F‐AV‐1451 in Alzheimer's disease (AD), we examined 30 cognitively healthy elderly (15 with preclinical AD), 14 prodromal AD, and 39 AD dementia patients. CSF T‐tau and P‐tau were highly correlated ( R = 0.92, P < 0.001), but they were only moderately associated with retention of 18 F‐AV‐1451, and mainly in demented AD patients. 18 F‐AV‐1451, but not CSF T‐tau or P‐tau, was strongly associated with atrophy and cognitive impairment. CSF tau was increased in preclinical AD, despite normal 18 F‐AV‐1451 retention. However, not all dementia AD patients exhibited increased CSF tau, even though 18 F‐AV‐1451 retention was always increased at this disease stage. We conclude that CSF T‐tau and P‐tau mainly behave as biomarkers of "disease state", since they appear to be increased in many cases of AD at all disease stages, already before the emergence of tau aggregates. In contrast, 18 F‐AV‐1451 is a biomarker of "disease stage", since it is increased in clinical stages of the disease, and is associated with brain atrophy and cognitive decline. Synopsis: Tau pathology is a key feature of Alzheimer's disease (AD) but the relationship between cerebrospinal fluid tau, the tau PET tracer 18 F‐AV‐1451 and other hallmarks of AD is unclear. This is now studied in a cohort of cognitively healthy controls and patients with prodromal and dementia stages of AD. Cerebrospinal fluid total‐tau and phosphorylated‐tau levels are moderately correlated with 18 F‐AV‐1451 tau PET retention. Correlations between cerebrospinal fluid tau and 18 F‐AV‐1451 tau PET are seen primarily in the dementia stage of Alzheimer's disease. Cerebrospinal fluid tau levels are increased already in preclinical AD. 18 F‐AV‐1451 tau PET is more strongly related to neurodegeneration and cognitive decline than cerebrospinal fluid tau levels are. Cerebrospinal fluid tau levels may be useful primarily to identify the presence of Alzheimer's disease, while 18 F‐AV‐1451 tau PET may be useful also to track the progression of the disease. Abstract : Tau pathology is a key feature of Alzheimer's disease (AD) but the relationship between cerebrospinal fluid tau, the tau PET tracer 18 F‐AV‐1451 and other hallmarks of AD is unclear. This is now studied in a cohort of cognitively healthy controls and patients with prodromal and dementia stages of AD.